Overexpression of oHIOMT results in various morphological, anatomical, physiological and molecular changes in switchgrass - Huang, Yanhua; Lai, Xianzhi; Liu, Changfa; Zhu, Wentao; Hao, Yongren; Zheng, Zehui; Guo, Kai (Frontiers in Plant Science, 2024)
Hydroxyindole O-methyltransferase (HIOMT) plays crucial role as the final enzyme in melatonin (N-acetyl-5-methoxytryptamine) synthesis. Overexpression of oHIOMT in switchgrass induces variations in melatonin levels, which influences the degree of morphological changes in transgenic plants. To determine the molecular mechanisms underlying the effect of HIOMT on switchgrass growth and stress resistance, we conducted comparative morphological, physiological, omics and molecular analyses between melatonin-moderate transgenic switchgrass, melatonin-rich transgenic plants and wild-type plants. We found that oHIOMT overexpression, with moderate melatonin levels, was crucial in regulating switchgrass growth through changes in cell size rather than cell number. Moderate melatonin levels were vital in regulating by modulating carbon fixation, stomatal development and chlorophyll metabolism. Regarding salt tolerance, melatonin activated numerous defence (e.g. morphological characteristics, anatomical structure, antioxidant enzymatic properties, non-enzymatic capacity and Na + /K + homeostasis). Additionally, oHIOMT overexpression altered lignin content and monolignol composition. Our study presents a comparative analysis of the functional significance and molecular mechanisms of melatonin in switchgrass, providing an important foundation for further analyses.